SIRT1 may play a crucial role in overload‐induced hypertrophy of skeletal muscle. (28th April 2017) - Koltai, Erika; Bori, Zoltán; Chabert, Clovis; Dubouchaud, Hervé; Naito, Hisashi; Machida, Shuichi; Davies, Kelvin JA; Murlasits, Zsolt; Fry, Andrew C; Boldogh, Istvan; Radak, Zsolt
Abstract : Key points: Silent mating type information regulation 2 homologue 1 (SIRT1) activity and content increased significantly in overload‐induced hypertrophy. SIRT1‐mediated signalling through Akt, the endothelial nitric oxide synthase mediated pathway, regulates anabolic process in the hypertrophy of skeletal muscle. The regulation of catabolic signalling via forkhead box O 1 and protein ubiquitination is SIRT1 dependent. Overload‐induced changes in microRNA levels regulate SIRT1 and insulin‐like growth factor 1 signalling. Abstract: Significant skeletal muscle mass guarantees functional wellbeing and is important for high level performance in many sports. Although the molecular mechanism for skeletal muscle hypertrophy has been well studied, it still is not completely understood. In the present study, we used a functional overload model to induce plantaris muscle hypertrophy by surgically removing the soleus and gastrocnemius muscles in rats. Two weeks of muscle ablation resulted in a 40% increase in muscle mass, which was associated with a significant increase in silent mating type information regulation 2 homologue 1 (SIRT1) content and activity ( P < 0.001). SIRT1‐regulated Akt, endothelial nitric oxide synthase and GLUT4 levels were also induced in hypertrophied muscles, and SIRT1 levels correlated with muscle mass, paired box protein 7 (Pax7), proliferating cell nuclear antigen (PCNA) and nicotinamide phosphoribosyltransferase (Nampt) levels. Alternatively, decreased forkhead box O 1 (FOXO1) and increased K48 polyubiquitination also suggest that SIRT1 could be involved in the catabolic process of hypertrophy. Furthermore, increased levels of K63 and muscle RING finger 2 (MuRF2) protein could also be important enhancers of muscle mass. We report here that the levels of miR1 and miR133a decrease in hypertrophy and negatively correlate with muscle mass, SIRT1 and Nampt levels. Our results reveal a strong correlation between SIRT1 levels and activity, SIRT1‐regulated pathways and overload‐induced hypertrophy. These findings, along with the well‐known regulatory roles that SIRT1 plays in modulating both anabolic and catabolic pathways, allow us to propose the hypothesis that SIRT1 may actually play a crucial causal role in overload‐induced hypertrophy of skeletal muscle. This hypothesis will now require rigorous direct and functional testing. Key points: Silent mating type information regulation 2 homologue 1 (SIRT1) activity and content increased significantly in overload‐induced hypertrophy. SIRT1‐mediated signalling through Akt, the endothelial nitric oxide synthase mediated pathway, regulates anabolic process in the hypertrophy of skeletal muscle. The regulation of catabolic signalling via forkhead box O 1 and protein ubiquitination is SIRT1 dependent. Overload‐induced changes in microRNA levels regulate SIRT1 and insulin‐like growth factor 1 signalling.